Educational Review: The Impact of Perinatal Oxidative Stress on the Developing Kidney - DeFreitas, Marissa J.; Katsoufis, Chryso P.; Benny, Merline; Young, Karen; Kulandavelu, Shathiyah; Ahn, Hyunyoung; Sfakianaki, Anna; Abitbol, Carolyn L. (Frontiers in Pediatrics, 2022)
Oxidative stress occurs when there is an imbalance between reactive oxygen species /reactive nitrogen species and antioxidant systems. The interplay between these complex processes is crucial for normal pregnancy and fetal development; however, when oxidative stress predominates, pregnancy related complications and adverse fetal programming such as preterm birth ensues. Understanding how oxidative stress negatively impacts outcomes for the maternal-fetal dyad has allowed for the exploration of antioxidant therapies to prevent and/or mitigate disease progression. In the developing kidney, the negative impact of oxidative stress has also been noted as it relates to the development of hypertension and kidney injury mostly in animal models. Clinical research addressing the implications of oxidative stress in the developing kidney is less developed than that of the neurodevelopmental and respiratory conditions of preterm infants and other vulnerable neonatal groups. Efforts to study the oxidative stress pathway along the continuum of the perinatal period using a team science approach can help to understand the multi-organ dysfunction that the maternal-fetal dyad sustains and guide the investigation of antioxidant therapies to ameliorate the global toxicity. This educational review will provide a comprehensive and multidisciplinary perspective on the impact of oxidative stress during the perinatal period in the development of maternal and fetal/neonatal complications, and implications on developmental programming of accelerated aging and cardiovascular and renal disease for a lifetime.